Morphological and molecular identifcation of sea cucumber species holothuria scabra, stichopus horrens and stichopus ocellatus from Kudat, Sabah, Malaysia - Kamarudin K.R.; Bahaman N.A.; Maryam Mohamed Rehan (Universiti Putra Malaysia, 2024)
Indexed by Scopus/ERA